(untitled) (LEARNing Landscapes, 2019)
In this paper I utilized the currere method and my experiences as a tenure track hire. Currere provided a framework that allowed me to remember and then engage my ways of knowing and immerse myself in supportive contexts. Specifically, I was able to deepen my understandings, learn, imagine up, and over time shift my tenure track stories. The complex, sometimes hegemonic institutional narratives embedded along my tenure track, regularly resulted in tension. In response to the tension and because of my enactment of the currere, I was able to remember and reflect on what I know and value, think about who I am and who I am becoming, including who I want to be as a professor. This work includes photographs because once I gave myself permission to play, taking, viewing, and manipulating pictures became part of my shifting tenure track identity stories.